2023
DOI: 10.1371/journal.ppat.1011741
|View full text |Cite
|
Sign up to set email alerts
|

A sporulation signature protease is required for assembly of the spore surface layers, germination and host colonization in Clostridioides difficile

Eleonora Marini,
Carmen Olivença,
Sara Ramalhete
et al.

Abstract: A genomic signature for endosporulation includes a gene coding for a protease, YabG, which in the model organism Bacillus subtilis is involved in assembly of the spore coat. We show that in the human pathogen Clostridioidesm difficile, YabG is critical for the assembly of the coat and exosporium layers of spores. YabG is produced during sporulation under the control of the mother cell-specific regulators σE and σK and associates with the spore surface layers. YabG shows an N-terminal SH3-like domain and a C-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 107 publications
0
3
0
Order By: Relevance
“…The genome assembly confirmed the presence of a prophage located within yabG (Figure 1). yabG encodes a sporulation-specific protease shown to regulate the assembly of the spore coat in both B. subtilis and C. difficile [23][24][25]27].…”
Section: Identification Of a Prophage-like Intervening Element In Yabgmentioning
confidence: 99%
See 2 more Smart Citations
“…The genome assembly confirmed the presence of a prophage located within yabG (Figure 1). yabG encodes a sporulation-specific protease shown to regulate the assembly of the spore coat in both B. subtilis and C. difficile [23][24][25]27].…”
Section: Identification Of a Prophage-like Intervening Element In Yabgmentioning
confidence: 99%
“…Since YabG is involved in the assembly of the spore surface in B. subtilis [24,25] and spore germination in C. difficile [26,27], we hypothesized that the presence/absence of the yin element could control the function of YabG and therefore alter the spore properties. Thermal destruction assays showed that the V73 spores were slightly less heat resistant than spores of ST7B (most heat-sensitive spore subpopulations, depicted in Figure 6 in the first 20 min of heating); however, the difference was not statistically significant for the most heat-resistant spore subpopulations (depicted in Figure 6 after the first 20 min of heating).…”
Section: Presence Of the Yin Element Does Not Affect Spore Heat Resis...mentioning
confidence: 99%
See 1 more Smart Citation